Freedom and Constraint in Engineered Noncolinear Polyketide Assembly Lines. Issue 2 (19th February 2015) - Sugimoto, Yuki; Ishida, Keishi; Traitcheva, Nelly; Busch, Benjamin; Dahse, Hans-Martin; Hertweck, Christian
Summary: Many pharmacologically important natural products are assembled by modular type I polyketide synthases (PKS), which typically act in a unidirectional fashion. The synthases producing the unusual nitro-substituted polyketides neoaureothin ( nor, also called spectinabilin) and aureothin ( aur ) are exceptional, as they employ individual modules iteratively. Here, we investigate the plasticity of the nor PKS and the factors governing the number of elongations catalyzed by the noncanonical module. Surprisingly, we observe that the nor PKS can mediate an additional chain elongation to yield the higher homolog homoneoaureothin. Furthermore, we design several truncated variants of the nor PKS to use them in the context of artificial assembly lines for aureothin and homoaureothin. The resulting polypropionate derivatives provide valuable insights into chain length control and reveal structure-activity relationships relating to the size of the polypropionate backbones. Overall, we show that iterative modules are remarkably adaptable while downstream modules are gatekeepers that select for correct polyketide chain length. Graphical Abstract: Highlights: Reconstitution and activation of the native neoaureothin pathway Rational PKS design gains insight into module gatekeeper functions Discovery and characterization of new members of neoaureothin/aureothin family First structure-activity relationships relating to size of polypropionate backbone Abstract : Sugimoto et al. achieved the heterologous expression of the neoaureothin pathway and rationally designed assembly lines by morphing the noncolinear polyketide synthase. The polypropionates generated provide valuable insights into chain length control and reveal structure-activity relationships relating to the size of the polypropionate backbones.